Human hepatic preneoplasia: phenotypes and proliferation kinetics of foci and nodules of altered hepatocytes and their relationship to liver cell dysplasia - Su, Qin; Benner, Axel; Hofmann, Walter J.; Otto, Gerd; Pichlmayr, Rudolf; Bannasch, Peter (Virchows Archiv, 1997)
Foci of altered hepatocytes (FAH) represent preneoplastic lesions, as shown in various animal models of hepatocarcinogenesis, but their significance in the human liver has not been established. The cellular composition, size distribution and proliferation kinetics of FAH in 163 explanted and resected human livers with or without hepatocellular carcinoma (HCC) and their possible association with small-cell change of hepatocytes (SCC) were therefore studied. FAH, including glycogen-storing foci, were found in 84 of 111 cirrhotic livers, demonstrating higher incidences in cases with (29/32) than in those without HCC (55/79). FAH were observed more frequently in HCC-free cirrhosis associated with hepatitis B or C virus or chronic alcoholic abuse (high-risk group) (37/47) than in that due to other causes (low-risk group) (12/21). MCF, predominant in cirrhotic livers of the high-risk group, were more proliferative, larger and more often involved in formation of nodules of altered hepatocytes (39.3%) than were GSF (8.5%). The results suggest that the FAH are preneoplastic lesions, MCF being more advanced than GSF. Oncocytic and amphophilic cell foci were also observed, but their significance remains to be clarified. Two types of SCC, namely diffuse and intrafocal SCC, were identified, but only intrafocal SCC was found to be related to increased proliferative activity and more frequent nodular transformation of the FAH involved, suggesting a close association with progression from FAH to HCC.